Differential patterns in mind perception in subclinical paranoia: relationships to self-reported empathy. Issue 2 (4th March 2017) - Buck, Benjamin; Hester, Neil; Penn, David L.; Gray, Kurt
ABSTRACT: Introduction: Although social cognition skills and biases are well-studied in paranoia, "mind perception" – perceiving the extent to which someone even possesses a thinking, feeling mind – is not. We sought to better characterise the profile of mind perception for individuals with paranoia. Methods: We examined links between mind perception and paranoia in a large ( n  = 890) subclinical sample. Participants completed measures of paranoia, schizotypy, mind perception, and dispositional empathy. These assessments were examined for their relationships to one another, as well as the possibility that mind perception partially mediates the relationship between paranoia and empathy. Results: Analyses revealed that increased paranoia was linked to less mind perception towards people. This distorted mind perception partially explained the link between paranoia and both perspective taking and empathic concern. Conclusions: In paranoia – and psychopathology more broadly – understanding and addressing distorted mind perception may be one component of restoring social functioning.